In situ surface electrochemical co-reduction route towards controllable construction of AuNPs/ERGO electrochemical sensing platform for simultaneous determination of BHA and TBHQ. (10th November 2015) - Yue, Xiaoyue; Song, Wensi; Zhu, Wenxin; Wang, Jianlong; Wang, Yanru
Graphical abstract: A green and cost-effective surface electrochemical co-reduction method was proposed to construct an electrochemical platform for simultaneous detection of BHA and TBHQ. Highlights: A green and cost-effective surface electrochemical co-reduction method was proposed. AuNPs/ERGO-based sensing platform was successfully constructed by this method. The constructed platform was firstly used for simultaneous detection of BHA and TBHQ. A good analytical performance towards the detection BHA and TBHQ was achieved. ABSTRACT: Herein, we demonstrated an in situ surface electrochemical co-reduction method to greenly and cost-effectively construct a gold nanoparticles/electrochemical reduced graphene oxide (AuNPs/ERGO) binary nanocomposites-based electrochemical sensing platform by using the mixture of graphene oxide (GO) and HAuCl4 coating on the surface of electrode as a precursor. GO was in situ electrochemically reduced to ERGO on the surface of electrode, accompanied by the simultaneous formation of AuNPs, which results in the fabrication of a conductive network of amorphous AuNPs/ERGO binary nanocomposite. Significantly, the resulting AuNPs/ERGO binary nanocomposite combines the advantages of AuNPs and ERGO, which exhibits an excellent performance towards simultaneous determination of BHA and TBHQ, allowing sensitive detection of BHA and TBHQ in the wide linear ranges of 0.1∼10 μg mL −1 and 0.1∼7 μg mL −1 with low limits of detection of 0.0419 μg mL −1 and 0.0503 μg mL −1, respectively. The practicability of this electrochemical sensing platform was realized in simultaneous detection of BHA and TBHQ in edible oil samples. The results indicate that the constructed electrochemical sensing platform presents satisfactory linear range, low detection limit, good accuracy and reproducibility. More importantly, the facile and environment-friendly surface electrochemical co-reduction strategy provided here maybe open a cost-effective way for setting up a binary nanocomposites or polynary nanohybrid-based electrochemical sensing platform, which benefits for extending the application of electrochemical sensor for the green, facile and sensitive analysis of electroactive compounds in food samples.